LATIHAN RENTANG GERAK ATAU RANGE OF MOTION (ROM) UNTUK MENINGKATKAN KEKUATAN OTOT PADA LANSIA BEDREST DENGAN GANGGUAN MOBILITAS FISIK DI BALAI SOSIAL LANJUT USIA MANDALIKA NTB - Heri Bahtiar; Maelina Ariyanti (Jurnal LENTERA, 2022)
Decreased muscle strength can cause disruption of functional abilities in the elderly because muscle strength affects almost all daily activities, so that the needs of the elderly can decrease and activity dependence on others. Mobilization problems that occur in the elderly can be overcome with non-pharmacological therapies such as progressive active and passive Range Of Motion (ROM) exercises that can increase muscle strength and maintain motor function. This service aims to increase muscle strength in bedrest elderly with impaired physical mobility with ROM. The number of elderly who will be given ROM is 30 elderly. The activity was carried out for 1 month by doing ROM to each room. The conclusion in this service is that there is an increase in strength in the elderly after ROM is performed. Suggestions in this service are expected for elderly social institutions to continue to provide guidance regarding ROM for bedrest elderly to increase muscle strength and support health.